2014
DOI: 10.1159/000366309
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Alprostadil in Diabetic Nephropathy: Possible Roles of Angiopoietin-2 and IL-18

Abstract: Background/Aims: To investigate the role of angiopoietin-2 (Ang-2) and IL-18 in the pathogenesis of diabetic nephropathy (DN) and the molecular mechanisms through which alprostadil protects renal function. Methods: DN was induced by streptozotocin and intraperitoneal injection of alprostadil was given to diabetic mice. After 2, 4 and 8 weeks of alprostadil treatment, the mRNA and protein expression of kidney Ang-2 and IL-18 were detected by reverse transcription PCR, Western blot and immunohistochemistry analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Previous studies have demonstrated that Morus alba exhibits comprehensive pharmacological effects that include, for example, hypoglycemic, immunomodulatory and antioxidant activities [19][20][21]. Our previous studies have found that RMP exerts hypoglycemic effect via regulating the intrapancreatic JNK/p38 pathway and blocking the IL-1/NF-κB pathway to protect against streptozotocin-induced apoptosis in pancreatic tissue and cytotoxicity in renal tissue [22][23][24]. Thus, we hypothesized that RMP might exert a beneficial effect on the development of DN.…”
Section: Mechanisms Of Protective Effect Of Ramulus Mori Polysaccharimentioning
confidence: 99%
“…Previous studies have demonstrated that Morus alba exhibits comprehensive pharmacological effects that include, for example, hypoglycemic, immunomodulatory and antioxidant activities [19][20][21]. Our previous studies have found that RMP exerts hypoglycemic effect via regulating the intrapancreatic JNK/p38 pathway and blocking the IL-1/NF-κB pathway to protect against streptozotocin-induced apoptosis in pancreatic tissue and cytotoxicity in renal tissue [22][23][24]. Thus, we hypothesized that RMP might exert a beneficial effect on the development of DN.…”
Section: Mechanisms Of Protective Effect Of Ramulus Mori Polysaccharimentioning
confidence: 99%
“…Ang-2 is stored in endothelial cell Weibel-Palade bodies, and high concentrations of Ang-2 produce marked impairment of endothelial function. Ang-2 is known to increase levels of proinflammatory cytokines 32 . In the present study, serum IL-19 levels were positively correlated with Ang-2, and also a positive correlation between IL-19 and HbA1c, HOMA-IR was observed, which shows that IL-19 was closely associated with glucose metabolism disorders and vascular lesions in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Murine glomerular endothelial cells (GEnCs) were purchased from Cell Biologics Company (C57-6014G) and were cultured according to the manufacturer's protocol and previously reports [16]. Cells were grown in Dulbecco's modified Eagle's medium (DMEM) (Gibco Invitrogen, LifeTechnologies, Scotland, UK) supplemented with 10% fetal bovine serum (FBS, Gibco Invitrogen).…”
Section: Methodsmentioning
confidence: 99%